Apprenticeship and entrepreneurial development in the Tanzania informal sector - Nsana Bernard; Knudsen Harald; Kristiansen Stein (Mzumbe University and Agder University College, 2026)
Entrepreneurship and the operation of small scale, "micro" firms in the informal sector play an important role in many developing economies. They provide employment and contribute to the creation of economic value in the nations. The acquisition of skills in the informal sector depends mainly on informal apprenticeship programs and experiential learning in the workplace. The study includes description of entrepreneurial roles and apprenticeship programs in different trades in the informal sector in Tanzania. It also explores the nature of innovation, economic performance, marketing and management in the sector.